Effect of Mobile Phone Position on the Visual and Driving Behaviour – A Lane Change Test-Based Study - Indresh Kumar VERMA; Bighna Kalyan NAYAK; Sougata KARMAKAR (Promet (Zagreb))
This study aims to investigate the effect of the position of mobile phones used for navigation purposes on the driving performance and visual behaviour of drivers. With the advancement of technology in recent times, drivers use mobile phone applications for navigation. Previous studies showed that drivers place their in-vehicle mobile phones at various locations. This behaviour could severely affect their driving performance and visual behaviour. Thirty drivers performed visual-manual tasks on mobile phones located at different positions (left, right, front and middle of the steering wheel) around the dashboard while driving in a simulated driving environment. The lane change test (LCT) assessed the driving behaviour, and the eye-tracker measured the visual behaviour. The outcome of LCT revealed that the best driving performance was achieved for mobile phones at the front of the steering wheel. The subjective workload rating score was the highest, and driving performance was worst for the middle mobile phone position. The findings of this study show that the in-vehicle mobile phone position has a significant effect on the driving performance and visual behaviour of the drivers. Insights drawn could be useful in drafting standard operating procedures for professional drivers and others in general.